A highly stable laccase from Bacillus subtilis strain R5: gene cloning and characterization. Issue 3 (4th March 2019) - Basheer, Saadia; Rashid, Naeem; Akram, Muhammad Sohail; Akhtar, Muhammad
ABSTRACT: The gene encoding copper-dependent laccase from Bacillus subtilis strain R5 was cloned and expressed in Escherichia coli . Initially the recombinant protein was produced in insoluble form as inclusion bodies. Successful attempts were made to produce the recombinant protein in soluble and active form. The laccase activity of the recombinant protein was highly dependent on the presence of copper ions in the growth medium and microaerobic conditions during protein production. The purified enzyme exhibited highest activity at 55 °C and pH 7.0. The recombinant protein was highly thermostable, albeit from a mesophilic source, with a half-life of 150 min at 80 °C. Similar to temperature, the recombinant protein was stable in the presence of organic solvents and protein denaturants such as urea. Furthermore, the recombinant protein was successfully utilized for the degradation of various synthetic dyes reflecting its potential use in treatment of wastewater in textile industry. Abbreviations: ABTS, 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid; CBB, Coomassie brilliant blue; SGZ, syringaldazine; DMP, 2, 2-dimethoxy phenol. Graphical abstract: : Decolourization of various synthetic dyes by recombinant Bsu -Lac. Laccase activity was measured without the addition of any metal ion in the reaction mixture.